Effect of long term ageing on γ' phase in spray formed FGH100L superalloy settled by different solution treatment - PENG Shi-qing; GE Chang-chun; TIAN Tian; HAO Zhi-bo; ZHAO Bo (Fenmo yejin jishu)
The effects of long term ageing on the size and morphology of γ' precipitations in the spray formed nickel-based superalloy FGH100L after subsolvs and supersolvs heat treatment (HT) were studied by scanning electron microscope (SEM). The results show that there are four kinds of γ' phases in the alloys after the subsolvs HT, and during the long term ageing, the sizes of primary, secondary, and large tertiary γ' phases increase while the size of small tertiary γ' phase decreases. None of these γ' phases grow in accordance with the coarsening kinetics as the Lifshitz, Slyozov, and Wagner (LWS) theory during the long term ageing. Apart from the small tertiary γ' phase, other three kinds of γ' phases began splitting in a similar way, and the secondary γ' phase shows the unstable protrusion after ageing for 500 h. No topological close packed (TCP) phase is found in the subsolvs HTed alloys. There are three kinds of γ' phases in the alloys after the supersolvs HT, and during the long term ageing, the primary γ' phase grows up slightly while the secondary and tertiary γ' phases show no obvious change. None of these γ' phases grow in accordance with the coarsening kinetics as LWS theory during the long term ageing. The morphology of primary and tertiary γ' phases changes little, and the secondary γ' phase is splitting at the early stage. No TCP phase is found in the supersolvs HTed alloys. The size and morphology variations of γ' phases in the supersolvs HTed alloys are smaller than those in the subsolvs HTed alloys, indicating that the former has the better microstructure stability.